The Effect of Medical Personnel Communication, Family Support, and Education on Treatment Adherence among Patients with Type 2 Diabetes Mellitus (DM) through Self-Efficacy as an Intervening Variable at the Internal Medicine Polyclinic of RSUD Dr. Harjono S. Ponorogo, East Java - Ariana Widiawati; Kemala Rita Wahidi; Nofierni Nofierni (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Medication non-adherence among patients with Type 2 Diabetes Mellitus (T2DM) remains a significant issue in chronic disease care. A preliminary study at the Internal Medicine Outpatient Clinic of Dr. Harjono S. Regional General Hospital in Ponorogo Regency revealed that 64% of patients took medication only when symptoms appeared, 70% had not received structured education, 58% did not understand the function of their medication, and 52% lacked family support. This study aimed to analyze the influence of of medical personnel communication, family support, and education on medication adherence, both directly and through self-efficacy as an intervening variable. The study employed a quantitative design using a cross-sectional approach and an explanatory research method. The sample consisted of 130 respondents selected via purposive sampling from a population of 178 active patients; the sample size was determined using the SEM-PLS rule of thumb. Data were collected using a fou point Likert scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). All research instruments were validated and proven reliable.The results indicate that medical personnel communication, family support, and education significantly influence medication adherence, both directly and through self-efficacy as an intervening variable. Self-efficacy was proven to be a significant mediator in enhancing medication adherence among T2DM patients. This study contributes to the development of hospital policies based on patient-centered care for the multidimensional management of chronic diseases.